2015
DOI: 10.1152/ajpendo.00391.2014
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of glucose metabolism by the renin-angiotensin-aldosterone system

Abstract: The renin-angiotensin-aldosterone system (RAAS) is an enzymatic cascade functioning in a paracrine and autocrine fashion. In animals and humans, RAAS intrinsic to tissues modulates food intake, metabolic rate, adiposity, insulin sensitivity, and insulin secretion. A large array of observations shows that dysregulation of RAAS in the metabolic syndrome favors type 2 diabetes. Remarkably, angiotensin-converting enzyme inhibitors, suppressing the synthesis of angiotensin II (ANG II), and angiotensin receptor bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 205 publications
(281 reference statements)
5
92
0
5
Order By: Relevance
“…Furthermore, increased catecholamine concentrations stimulate hepatic glycogenolysis and gluconeogenesis leading to increased circulating glucose. Heart failure is also associated with hyperactivation of the renin-angiotensin-aldosterone system (RAAS), system, which has been implicated in the pathophysiology of insulin resistance 96 . In addition to increasing circulating concentrations of angiotensinogen (originating from adipose tissue) 97 , chronic hyperinsulinemia may also increase the expression of angiotensin II receptors, which may further exacerbate adverse left ventricular remodeling 98 .…”
Section: Insulin Resistancementioning
confidence: 99%
“…Furthermore, increased catecholamine concentrations stimulate hepatic glycogenolysis and gluconeogenesis leading to increased circulating glucose. Heart failure is also associated with hyperactivation of the renin-angiotensin-aldosterone system (RAAS), system, which has been implicated in the pathophysiology of insulin resistance 96 . In addition to increasing circulating concentrations of angiotensinogen (originating from adipose tissue) 97 , chronic hyperinsulinemia may also increase the expression of angiotensin II receptors, which may further exacerbate adverse left ventricular remodeling 98 .…”
Section: Insulin Resistancementioning
confidence: 99%
“…In humans, obesity is associated with mildly increased serum thyroid-stimulating hormone and triiodothyronine concentrations, 66 increased serum growth hormone (but not insulinlike growth factor-1) concentrations, 67 increased circulating concentrations of angiotensinogen, renin, angiotensin-converting enzyme, and aldosterone, 68 and low androgen levels. 67 The functional implications of most of these changes are not well-understood, although obesity is known to interfere with reproductive capability, 69 and changes in the components of the renin-angiotensin-aldosterone system are thought to contribute to oxidative stress and altered glucose metabolism.…”
Section: Obesity and Other Endocrine Abnormalitiesmentioning
confidence: 99%
“…67 The functional implications of most of these changes are not well-understood, although obesity is known to interfere with reproductive capability, 69 and changes in the components of the renin-angiotensin-aldosterone system are thought to contribute to oxidative stress and altered glucose metabolism. 68 In dogs and cats, information about the effects of obesity on these variables is limited. No increase in thyroid-stimulating hormone was found with weight gain in cats, although free T4 was increased with obesity, likely because of increased NEFA concentrations.…”
Section: Obesity and Other Endocrine Abnormalitiesmentioning
confidence: 99%
“…Recent findings suggest a pivotal role of aldosterone in the pathogeneses of inflammation, insulin resistance and metabolic syndrome [12,13]. Evidence indicates that a high level of aldosterone leads to a greater prevalence of hyperglycemia and induces a high rate of cardiovascular events [14]. Moreover, recent studies have revealed that aldosterone treatment increases the mRNA levels of tumor necrosis factor-α (TNFα) and interleukin-6 (IL-6) and inhibits adiponectin mRNA expression; however, the possible mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%